Prevalence and economic impact of cystic echinococcosis and liver fluke infections in slaughtered sheep and goat in north-central Iran, 2008–2018 - Najjari, M. (J Parasit Dis, 2019)
Cystic echinococcosis (CE) and liver fluke infections as important zoonotic infections impose a large socioeconomic impact on societies. As an endemic region for these infections, slaughterhouse inspections should be more considered in Iran. This study aimed to analyze the 11-year record of offal condemnation due to CE, fascioliasis, dicrocoeliasis infections in sheep and goat and its economic impact at Alborz slaughterhouse, north-central Iran. The prevalence rate was calculated as the infected organs (as nominator) divided by the slaughtered cases (as the denominator) in each year and month. The annual percent changes was used to determine trends of parasitic diseases over time. The relationship between metrological indexes and the prevalence of parasitic diseases was determined by the linear regression model. Statistical analyses were done using STATA software 14. For an estimate, the economic impact, the total numbers of offal condemnation were calculated. The overall prevalence rate of fascioliasis, dicrocoeliasis, and CE was 0.95%, 2.17%, and 12.74%, respectively. There was a declining trend in the prevalence of fascioliasis and dicrocoeliasis, whereas, the prevalence of CE increased from 7.57% in 2008 to 9.53% in 2018, representing an annual change of + 0.02%. The direct economic impact was estimated at US$ 1,670,977 and US$ 25,148 for liver and lung, respectively. The number of condemned organs due to these infections is noticeable in Alborz Province, north-central, Iran. The high economic impact of these infections showed the necessity of implementing a continuously infected animal’s trace-back and disease control in the site of infection.